Peningkatan Prestasi Belajar dengan Model Pembelajaran Picture and Picture pada Sekolah Menengah Pertama - Markamah, Umul (Jurnal Didaktika Pendidikan Dasar, 2023)
This research is a classroom action research that aims to improve students’ learning achievement using the Picture and Picture learning model. This research consisted of three cycles divided into six meetings. Each cycle includes planning, implementation, observation and reflection activities. Data collection uses observation techniques while learning achievement uses simple statistics. The results of the research show that using the Picture and Picture learning model can increase the activities of students and teachers during the learning process. The increase in student learning achievement was marked by (a) an increase in cognitive scores (average daily test), namely from 65.53 in cycle 1, 71.46 in cycle 2, and 74.61 in cycle 3; (b) increase in affective value from 164 in cycle 1, 189 in cycle 2, to 194 in cycle 3; and (c) an increase in completeness from 47.37% in cycle 1, 57.89 in cycle, to 68.42% in cycle 3. The results of this study are expected to increase teacher professionalism and improve student achievement.